Meta Analisis: Penerapan Media Pembelajaran Google Sites pada Pembelajaran IPA - Hayunnita, Nur; Yuliani, Hadma; Nasir, Muhammad (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Learning Natural Sciences has not yet obtained satisfactory results even though students have been studying science since they were in Elementary School (SD), therefore media is needed that can help students to improve the quality of learning. One of them is by providing Google Sites learning media for science learning. The purpose of this meta-analysis is to determine the effect of implementing Google Sites learning media on science learning. This meta-analytic research method consists of formulating the problem, collecting data (study), coding the data, and analyzing the data and interpreting it. From the results of the article search, it was obtained 20 articles that influenced the development of Google sites learning media on science learning. There are 7 articles that meet the criteria for inclusion: when the learning process uses Google sites in science learning. This review reveals that there is a strong positive effect from the influence of developing Google sites learning media on science learning. The findings of this study revealed that the results of the meta-analysis obtained an effect size of the influence of the development of Google sites learning media on science learning of 1.6 which is classified as high, namely 95%.